2016
DOI: 10.1007/s00127-016-1170-2
|View full text |Cite
|
Sign up to set email alerts
|

Key successes and challenges in providing mental health care in an urban male remand prison: a qualitative study

Abstract: PurposeThis study aimed to describe the workings of an urban male remand prison mental health service exploring the key challenges and successes, levels of integration and collaboration with other services.MethodA purposive sampling was used to recruit key prison and healthcare professionals for in-depth interviews. A thematic analysis was used to analyse transcripts based on an initial coding frame of several predefined themes. Other key themes were also identified.ResultsTwenty-eight interviews were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
20
0
3
Order By: Relevance
“…Nineteen empirical studies were included (see Appendix A). Eight of these had quantitative designs (Bond and Gittell 2010;Fletcher et al 2009;Friestad and Kjelsberg 2009;Hean, Ødegård and Willumsen 2017;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017) and 11 had qualitative designs (Denton 2014;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Hansen 2015;Hean, Willumsen and Ødegård 2017a;Hean, Willumsen and Ødegård 2017b;Kras 2012;Moore and Hamilton 2016;Samele et al 2016;Yamatani and Spjeldnes 2011). The samples originated in Norway (Friestad and Kjelsberg 2009;Hansen 2015;Hean, Ødegård and Willumsen 2017;Ødegård 2017a, 2017b), the USA (Bond and Gittell 2010;Fletcher et al 2009;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Kras 2012;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017;Yamatani and Spjeldnes 2011), Australia (Denton 2014), and the UK (Moore and Hamilton 2016;Samele et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen empirical studies were included (see Appendix A). Eight of these had quantitative designs (Bond and Gittell 2010;Fletcher et al 2009;Friestad and Kjelsberg 2009;Hean, Ødegård and Willumsen 2017;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017) and 11 had qualitative designs (Denton 2014;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Hansen 2015;Hean, Willumsen and Ødegård 2017a;Hean, Willumsen and Ødegård 2017b;Kras 2012;Moore and Hamilton 2016;Samele et al 2016;Yamatani and Spjeldnes 2011). The samples originated in Norway (Friestad and Kjelsberg 2009;Hansen 2015;Hean, Ødegård and Willumsen 2017;Ødegård 2017a, 2017b), the USA (Bond and Gittell 2010;Fletcher et al 2009;Friedmann et al 2012;Gunnison and Helfgott 2017;Hannaa et al 2020;Kras 2012;Lehman et al 2009;Orrick et al 2011;Shavit et al 2017;Wooditch, Sloas and Taxman 2017;Yamatani and Spjeldnes 2011), Australia (Denton 2014), and the UK (Moore and Hamilton 2016;Samele et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The overriding aim of this research study was to explore the effectiveness of an exercise referral scheme as a health promotion intervention for Irish male prisoners with mental health symptoms, using a mixed methods design. The literature confirmed that imprisoned people have extraordinarily high levels of poor mental health and indicated several reasons why this is the case, highlighting social, economic and genetic circumstances as some of the main causes (Mannocci et al, 2015;Hoke 2015;Samele et al, 2016). It is clear from the literature reviewed that prisoners are known to experience mental illness to varying degrees and with many consequences, which range from mild anxiety and depression, to chronic self-harm and even suicide.…”
Section: Discussionmentioning
confidence: 95%
“…In a time of economic constraint, it is unclear how feasible this is. Alternative models of PMHS have been proposed, including the contentious topic of designated ‘prison hospitals’, 19 , 20 as are present across areas of Europe and the USA. 21 23 However, there are ethical implications for implementing services of this type.…”
Section: Discussionmentioning
confidence: 99%